Metaverse applications for intelligent healthcare - Zaman, Noor 1972-; Gaur, Loveleen (IGI Global, 2024)
Metaverse Applications for Intelligent Healthcare explores the exciting intersection of artificial intelligence (AI) and the metaverse in the field of healthcare. The use of AI technology in healthcare has already shown great potential in assisting with diagnosis, treatment, and patient care. The metaverse, with its immersive virtual environments, has the potential to revolutionize healthcare by making it more accessible, efficient, and personalized.This book introduces various applications of the metaverse in healthcare, including virtual consultations, remote patient monitoring, and virtual rehabilitation. The book discusses how the metaverse can be used to provide immersive experiences that empower patients and providers, while also offering unique learning opportunities. The book is ideal for researchers, practitioners, healthcare professionals, scholars, and students who are interested in exploring the cutting-edge technology of AI and the metaverse in healthcare. It offers insights into the future of healthcare, and how these technologies can be used to provide better care to patients. By combining the latest research in AI and the metaverse, this book provides a comprehensive overview of the potential applications of these technologies in healthcare.